Application of Technology Acceptance Model on Database Normalizer - Al-Absi, Ahmed Abdulhakim Ahmed (2011)
Normalization is one of the most important activities in database designing. The good database design is the database that meets user requirements and designed its structure carefully. Therefore, this study focused on developing a database normalization application that helps database designers to perform the normalization process automatically and improves the database designing by avoiding the problems of carrying out normalization manually which has many drawbacks such as time consuming, prone to errors and requires more than one skilled user. The main objective of this study is to develop a database normalizer application to normalize the database tables up to the third normal form (3NF). This study provides a normalization algorithm to perform the 1NF, 2NF, and 3NF automatically based on Microsoft Access and SQL Server databases. Experiment was conducted to check the functionality in performing the normalization process. The experiment result showed that the prototype achieved the result successfully as expected and fulfills the requirements and rules of normalization processes. Moreover, a questionnaire based on the Technology Acceptance Model technique has been adopted to ensure of the prototype level in terms of easiness of use, and satisfaction.